(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
This article covers the factors affecting the financial stability of insurance companies and the stages of their management. Also, the scientific-theoretical views of economists who studied the concept of "financial stability" are widely covered. In addition, the classification of the types of financial stability of insurance companies and the classification of indicators according to the criteria for evaluating the financial condition are highlighted. In addition, the article provides conclusions and suggestions on the factors affecting the financial stability of insurance companies and the stages of their management.